Oral therapy extension programme: half yearly report, January-June 1985, phase II - BRAC (© BRAC, 2016)
1. Introduction 2. Working strategy and methodology 3. Programme performance 4. Impact evaluation 5. Chloride concentration 6. IGS usage survey